Childhood and adolescent obesity in cardiorenal metabolic syndrome and Type 2 diabetes: a clinical vignette and ultrastructure study. (November 2011) - Hayden, Melvin R; Joginpally, Tejaswini; Salam, Muhammad; Sowers, James R
SUMMARY Childhood–adolescent overweight and obesity (CAOO) have grown to pandemic proportions during the past decade. The younger onset of obesity will have dire future complications manifesting as earlier onset end-organ disease in a disproportionate number of younger adults. This clinical snapshot begins with a clinical vignette of a 13 year old female with obesity, atherogenic lipid profile, hypertension with early urinary changes of chronic kidney disease and prediabetes. We have focused on the early ultrastructural changes found in two rodent models of obesity (Zucker obese [fa/fa] rat model of obesity, insulin resistance and prediabetes and db/db mouse model of obesity, insulin resistance and Type 2 diabetes mellitus) in their adolescent ages. Our focus is on remodeling in the obese adipose tissue, emphasizing the omental depot, the skeletal muscle, the islet and ββ cells and the end-organs including the myocardial and renal tissues. Obesity seems to be the driving force behind this process occurring in the skeletal muscle, islet and ββ cells, which constitutes the adipose–skeletal muscle–islet axis in the development of Type 2 diabetes mellitus. This current epidemic–pandemic of CAOO causes a red flag to be raised in order to have primary-care providers become more involved and understand this complex problem. The CAOO pandemic may alter the future course of human disease unless we as primary-care physicians intervene. For the first time the current generation may not live to be as old as their parents.